2015
DOI: 10.1152/japplphysiol.00608.2014
|View full text |Cite
|
Sign up to set email alerts
|

Sodium nitrite supplementation improves motor function and skeletal muscle inflammatory profile in old male mice

Abstract: Aging is associated with motor declines that lead to functional limitations and disability, necessitating the development of therapies to slow or reverse these events. We tested the hypothesis that sodium nitrite supplementation attenuates declines in motor function in older C57BL/6 mice. Motor function was assessed using a battery of tests (grip strength, open-field distance, rota-rod endurance) in old animals (age 20-24 mo) at baseline and after 8 wk of sodium nitrite (old nitrite, n = 22, 50 mg/liter) or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 61 publications
(87 reference statements)
1
27
0
1
Order By: Relevance
“…Salivary nitrite can then be metabolised to NO in the stomach by a variety of reductase enzymes before entering the circulation; hence, this process is known as the nitrate-nitrite-NO pathway (Clifford et al 2015;Hobbs et al 2012;Lundberg et al 2008). Augmenting NO bioavailability has been shown to exhibit biological effects that might be of benefit for exercise performance, such as vasodilation and improved contractile efficiency (Jones 2014); however, in addition, a number of recent animal studies have also revealed that it might attenuate inflammation (Justice et al 2015) and inhibit exercise-induced muscle proteolysis (i.e., calpain activation), preserving muscle function (Lomonosova et al 2014). This raises the possibility that NO donors, such as beetroot, might also help to enhance recovery after muscle-damaging exercise in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary nitrite can then be metabolised to NO in the stomach by a variety of reductase enzymes before entering the circulation; hence, this process is known as the nitrate-nitrite-NO pathway (Clifford et al 2015;Hobbs et al 2012;Lundberg et al 2008). Augmenting NO bioavailability has been shown to exhibit biological effects that might be of benefit for exercise performance, such as vasodilation and improved contractile efficiency (Jones 2014); however, in addition, a number of recent animal studies have also revealed that it might attenuate inflammation (Justice et al 2015) and inhibit exercise-induced muscle proteolysis (i.e., calpain activation), preserving muscle function (Lomonosova et al 2014). This raises the possibility that NO donors, such as beetroot, might also help to enhance recovery after muscle-damaging exercise in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Our initial hypothesis was that, akin to other functional foods shown to attenuate exercise-induced muscle damage (EIMD), such as cherry juice (Bell et al 2014;Bell et al 2015;Bowtell et al 2011;Connolly et al 2006;Howatson et al 2010) and pomegranate juice (Trombold et al 2010;Trombold et al 2011), it could be through an anti-inflammatory or antioxidant (AOX) related mechanism. Nonetheless, it is equivocal as to whether beetroot juice and/or its constituents are effective AOXs, with some studies suggesting not (Whitfield et al, 2016;Larsen et al, 2014) and others showing reductions in oxidative stress and inflammatory markers (Clifford et al 2015;El Gamal et al 2014;Jadert et al 2012;Justice et al 2015;Pietrzkowski et al 2010;Ashor et al, 2016). Notwithstanding the disparate findings to date, it is conceivable that AOX or anti-inflammatory effects could help to dampen the acute secondary muscle damage response after an exercise bout-the hallmarks of which are proposed to be oxidative stress, inflammation and muscle proteolysis-and this could facilitate a faster recovery of muscle function and/or reduction in muscle pain (Howatson & van Someren, 2008;Sousa et al 2014;Urso 2013).…”
Section: Introductionmentioning
confidence: 99%
“…NO plays an important role in skeletal muscle physiology, including regulating inflammatory processes during muscle repair . A recent study of aging mice revealed that 8‐week sodium nitrite supplementation reduced proinflammatory cytokines in skeletal muscles and improved physical performance . In another study, NO administration significantly reduced myoinjury‐induced increase in intramuscular proinflammatory cytokines, such as TNF‐α and IL‐6.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) bioavailability is instrumental in skeletal muscle physiological processes, including inflammatory regulation . A recent study of aging mice revealed that sodium nitrite (NO donor) improved physical performance parameters, such as grip strength, through its anti‐inflammatory effects on skeletal muscles . A study using younger mice reported contradictory results: Nω‐nitro‐L‐arginine methyl ester hydrochloride (NO synthesis [NOS] inhibitor) significantly increased myoinjury‐induced intramuscular inflammation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation